Impact of a multi-strain L. crispatus-based vaginal synbiotic on the vaginal microbiome: a randomized placebo-controlled trial - Jacques Ravel; Sheri Simmons; Eleni Greenwood Jaswa; Sara Gottfried; Miriam Greene; Susan Kellogg-Spadt; Dirk Gevers; Diane M. Harper (npj Biofilms and Microbiomes)
Abstract A clinical trial of a multi-strain vaginal synbiotic (NCT05659745, registered 12/19/2022 at clinicaltrials.gov) led to an optimal vaginal microbiome dominated by L. crispatus (CST I). The synbiotic led to a significant increase in L. crispatus compared to placebo (p < 0.05), and conversion to CST I was significantly higher with the vaginal synbiotic than with placebo (90 vs 11%; p < 0.002). Mechanistically, the synbiotic reduced Gardnerella vaginalis and Candida, clinically important microbes.